INVITATION TO JOIN A COURSE: DESCRIPTIVE SENSORY ANALYSES FOR INDUSTRIAL APPLICATIONS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 6 May 2016 The School of Industrial Technology, Universiti Sains Malaysia (USM) will be organising a 3day Course on Descriptive Sensory Analyses for Industrial Applications, which will be held on 15, 16 & 17 August 2016, from 9:00 am until 5:00 pm at the Food Technology Division, School of Industrial Technology, USM, Penang.